Power of the Priests: political use of religious knowledge - Kubisch, Sabine; Klinkott, Hilmar (De Gruyter, 2023)
Religion plays a central role in nearly every aspect in people’s life of most pre-modern cultures. Especially the interconnection between religion and politics is a common fact but the details of this relation and interacting processes behind this are not substantially studied. Therefore, this volume does not aim to confirm the linkage of religion and politics in general but to investigate its functionalities in political processes. A focus is placed on the political role of religious personnel beyond their religious and cultic tasks and their influence in pre-modern societies from a cross-cultural perspective. Specialists from various disciplines present their research based on case studies. Thereby this interdisciplinary volume covers a wide geographical and chronological range from ancient Egypt in the Bronze Age until medieval England. These papers are organised according to core functions questioning the instrumentalisation of religious personnel.